Application of the K-Nearest Neighbor Method in Determining Web-Based Early Childhood Development - Rahmat Hidayat (Journal of Computer Engineering, Electronics and Information Technology, 2023)
Childhood is a period of rapid growth and development, so it is often termed as the golden period as well as the critical period. The golden period can be realized if at this time infants and children obtain suitable nutritional intake for optimal growth of flowers. But during this time Posyandu process is still done manually, so in providing the nutritional status information children must wait long. System that is able to assist in solving the problem is the Decision Support System (SPK) with the method K-Nearest Neighbor (KNN) that can produce information on the nutritional status of children that is the status of poor nutrition obtained from the calculation of weight /Age, very short status is obtained from the calculation of height/age, and very skinny status obtained from calculation of weight/height. And hopefully this system can be used in Posyandu to monitor the growth of children so that children with less nutritional status and poor nutrition get better and faster handling. The design of this decision support system uses a Web-based system with PHP programming language and a MySQL database for the web to be easily accessed.